The Relationship Among Financial Inclusion, Non-Performing Loans, and Economic Growth: Insights From OECD Countries - Zhang, Peng; Zhang, Mengxue; Zhou, Qiancheng; Zaidi, Syed Anees Haider (Frontiers in Psychology, 2022)
This study investigates the linkages among financial inclusion, non-performing loans (NPLs) and economic growth. The study uses large panel data of 21 Organization for Economic Corporation and Development (OECD) countries for dynamic panel estimation by using Driscoll-Kraay standard errors with fixed effect. The results of the dynamic panel estimation technique revealed the existence of long-run relationships among financial inclusion, NPLs and economic growth. Financial inclusion contributes positively in economic growth reducing NPLs. Further, NPLs negatively impact financial inclusion as well as economic growth. The study presents important policy recommendations to control non-performing loans and to boost the level of financial inclusion in the selected economies.